Teaching Grammar Through Reading Text Strategy - Widi, Rahma; Pratama, Eggi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study discussed the strategy of teaching grammar through reading texts as an effective and efficient strategy to improve students' understanding of grammar. By instructing the grammar in the reading lesson, the students enhance a deeper understanding of both grammar rules and the text they are reading. This article discussed the impact of teaching grammar through reading the text and provides beneficial strategies for implementing the strategy in the classroom. The method used in this study was descriptive research as the research design. The participants in this study consisted of 40 students from the Faculty of Computer Science taking English courses in the first semester who were categorized as English for Specific Purposes (ESP) when the data was collected. The participants were divided into two classes with each class containing 20 students. The result of this study found that these two strategies were efficient to be taught for teaching grammar.